Nilai Moderasi Beragama Pada Tradisi Upacara Kremasi Jenazah Di Desa Rama Agung - Syafri, Fatrica; D, Luh Ratu Ayu; Lestari, Puja; P, Nabila Fasyiha; Muzandi, Viki; Azayno, Bintang (Pakis Journal Institute, 2024)
The aim of this service is to strengthen the attitude of religious moderation by understanding and practicing the value of moderation in Rama Agung Village. It is hoped that this can make a positive contribution to the development of attitudes of tolerance and harmony in society. This research describes a series of procedures from the beginning to the end of cremation in Lama Agung village. Apart from that, this research also examines how the value of religious moderation is applied in a very harmonious and mutually supportive society. This research aims to provide a deeper understanding of the application of facilitation in the context of community diversity and harmony in the village by explaining the details of the cremation process and social interactions that occurred while I was here. The qualitative approach of this research is to collect primary data through interviews with Hindu traditional leaders who are directly involved in the implementation of the Ngaben ceremony. This method helps us to understand more comprehensively the aspects of ritual and religious facilitation in Rama Agung village. The results of this research show that the cremation death ritual includes several stages, namely preparation of offerings and equipment, handover of the body, implementation of the cremation ceremony, and reading of praise songs. Collection and disposal of ashes, closing of the event and evening prayer at Mentebengan.